Three-Step Stacking by Field-Enhanced Sample Injection, Sweeping, and Micelle to Solvent Stacking in Capillary Electrophoresis: Anionic Analytes - Grochocki, Wojciech (Archīum Ateneo, 2016)
Three-step stacking by field-enhanced sample injection (FESI), sweeping, and micelle to solvent stacking (MSS) in co-EOF capillary zone electrophoresis (CZE) is presented for anionic analytes. Long FESI produced an overloaded stacked zone of analytes (four model penicillins). Sweeping of the FESI zone was by electrokinetic injection of cetyltrimethylammonium bromide (CTAB) micelles. MSS was by short injection of 60% methanol that released the swept analytes from CTAB micelles. The sensitivity enhancement factors were 146–279 and 519–954 for conductivity ratio of 10 and 100, respectively. The SEF enhancement factors (factor = SEF from three-step stacking/SEF from FESI) were 16–32 and 6–10, correspondingly. The LODs were between 6.6–13.2 ng/mL, repeatability (intraday and interday) was %RSD ≤ 5.4%, and linearity was R2 ≥ 0.998. Application to real sample was investigated using fortified plasma after liquid–liquid extraction.